THWARTING THE "MERCHANTS OF DEATH" ACCUSATION: THE POLITICAL ECONOMY OF MILITARY PROCUREMENT IN INDUSTRIAL DEMOCRACIES DURING THE INTERWAR PERIOD - Jari Eloranta; Mark Wilson (Essays in Economic and Business History, 2010)
This article charts the interwar military procurement practices of several democratic states, concentrating on the United States, the United Kingdom, Sweden, and Finland. In addition to comparing some of the foundations of the Allies' successful industrial mobilization in World War II, this article concludes that interwar procurement practices in some of the most liberal democracies were surprisingly resistant to capture by business interests. This finding suggests that in describing this era, we should be cautious about ascribing causal power to trans-historical economic behaviors such as rent-seeking and collusion, without taking into account the institutional setting in which such activities took place. The record of the interwar period suggests that democracies can use bureaucratic administration and public enterprise to establish robust barriers to rent-seeking and corruption in the military economy. During the interwar period, these administrative barriers were erected in conjunction with intense public concern about military profiteering. Whether they would be less effective in different ideological environments deserves further investigation.